Management of Dadru Kushtha (Tenia corporis)—A Case Report - Trupti Thakre; Sourabh G. Deshmukh; Neha Chavhan (Journal of Pharmacy and Bioallied Sciences)
Dadru is one of the Kapha–Pitta Pradhana Twak Vikara. It is a chronic disease in which Tridosha are involved so Rakta shodhak and Tridoshaghna along with Kushtaghna Chikitsa give better relief in Dadru. A 32-year-old male patient approached the outpatient department (OPD) of Mahatma Gandhi Ayurveda Hospital, Salod, Wardha, Maharashtra, with a chief complaint of round reddish patches over the axilla with severe Kandu (Itching), Daha (burning sensation), elevated circular lesions, and Raag (erythema). After 15 days of treatment, the patient got relief from all the symptoms by taking proper medicines like Gandhak Rasayan, Panchatikta ghrita, 777 oil, and fungiwin cream. Due to Kushtaghna and the immunity booster properties of drugs, the present case study revealed the efficacy of Ayurveda by Shaman Chikitsa for 15 days in managing Dadru.